2021
DOI: 10.35848/1347-4065/ac15a7
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen infiltration into BaTiO3-based dielectrics for multi-layer ceramic capacitors under highly accelerated temperature and humidity stress test

Abstract: To make electrical devices, such as smartphones and automotive devices, more functional, the mechanism of electrical reliability in multi-layer ceramic capacitors (MLCCs) under high temperature, high humidity, and electric field bias environments has been studied. Although it has been presumed that hydrogen influences this mechanism, it is difficult to analyze hydrogen itself. Therefore, we investigated BaTiO 3 -based dielectrics in which the leakage current increases by conducting highly accelerated temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Moreover, BiFeO 3 has a Curie temperature (T C ) of 830 °C, 47,48) which is much higher than that of PbTiO 3 (495 °C49) ) Barium titanate, BaTiO 3 , play an essential role for ceramic capacitor applications 50,51) and also for ferroelectricderived functions. [52][53][54][55][56] In tetragonal P4mm symmetry, Ti and Ba are displaced cooperatively along the polar c axis, leading to a P s of 26-29 μC cm −2 . 57,58) For (1−x) BiFeO 3 -x BaTiO 3 ceramics, structural analysis showed that an x increase changes a crystal symmetry from R3c rhombohedral to pseudo-cubic at ca.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BiFeO 3 has a Curie temperature (T C ) of 830 °C, 47,48) which is much higher than that of PbTiO 3 (495 °C49) ) Barium titanate, BaTiO 3 , play an essential role for ceramic capacitor applications 50,51) and also for ferroelectricderived functions. [52][53][54][55][56] In tetragonal P4mm symmetry, Ti and Ba are displaced cooperatively along the polar c axis, leading to a P s of 26-29 μC cm −2 . 57,58) For (1−x) BiFeO 3 -x BaTiO 3 ceramics, structural analysis showed that an x increase changes a crystal symmetry from R3c rhombohedral to pseudo-cubic at ca.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, it was presumed that when water vapor infiltrated the interface between the anode-side inner electrode and the dielectric, electrolysis occurred at the interface, as shown in the equation below, and D + was attracted to the cathode-side inner electrode by migration through the dielectric. [23][24][25] Considering the results of Fig. 3(a) and the aforementioned presumption, the deuterium in the dielectric is presumed to exist as D +…”
mentioning
confidence: 95%
“…It was observed, that deuterium was biased toward the cathode-side inner electrode in the BaTiO 3 -based dielectric exhibiting increased leakage current. 25) Therefore, the increased leakage current in the test can be attributed to either the proton migration at the interstitial sites in the dielectric lattices or the corresponding increase in the electron concentration. 25) The mechanism of proton migration could be either diffusion due to the concentration gradient or drift due to the voltage bias.…”
mentioning
confidence: 99%
See 2 more Smart Citations